Hospital Medical and Nursing Managers’ Perspectives on Health-Related Work Design Interventions. A Qualitative Study - Genrich, Melanie; Worringer, Britta; Angerer, Peter; Müller, Andreas (Frontiers in Psychology, 2020)
BACKGROUND: Research indicates that the active support of managers is essential for the sustainable implementation of health-related work design interventions in organizations. However, little is known about managers’ perceptions of such health promotion measures. OBJECTIVE: Our study aims to provide information that help to foster managers active support of health-related work design interventions in hospitals. Based on Ajzen’s Theory of Planned Behavior (TPB) we explore the attitudes, perceived organizational norms, and perceived behavioral control of managers in the hospital regarding such interventions. METHODS: Semi-structured interviews with 37 managers (chief physicians, senior physicians, and senior nurses) were carried out in one German hospital. A software aided qualitative content analysis was applied. RESULTS: We observed that the majority of managers are aware of the importance of health-related work design. We found a high variation in the perception of organizational norms related to mental health promotion of employees. Behavioral control for supporting interventions is perceived more on an individual (e.g. appraisal interviews, professional development or support) and team level (e.g. fair work schedule, regular team meetings), less on an organizational level. CONCLUSIONS: To enable and to motivate hospital medical and nursing managers to support health-related work design, hospitals need to establish clear organizational norms that the health promotion of their employees is an important organizational goal. Moreover, managers need to get more work-design competencies and decision latitude to get more control. Important arguments for the top hospital management could be that health-related work design is highly effective for economic success, for treatment quality, and that the middle management already has a positive attitude towards the implementation of measures that help promote the mental health of their staff.